Tribology-optimised silk protein hydrogels for articular cartilage repair. (September 2015) - Parkes, Maria; Myant, Connor; Dini, Daniele; Cann, Philippa
Abstract: Porous hydrogels were made from silk fibre as potential materials for cartilage repair. The aim was to develop materials which mimicked the tribological behaviour of cartilage, with controlled pore-sizes and optimised mechanical properties. Mechanical tests showed hydrogels had a comparable compressive modulus to cartilage, with stiffness improved by decreasing pore size. Under static loading and during shear hydrogels demonstrated significant interstitial fluid support. Friction testing showed the hydrogels had a cartilage-like frictional response, dominated by this interstitial fluid support. Silk hydrogels showed little wear, early signs of which were changes in surface morphology that did not correlate with the equilibrium friction coefficient. Consequently both wear and friction should be monitored when assessing the tribological performance of hydrogels. Graphical abstract: Highlights: Silk hydrogels with controlled pore sizes between 10 and 40 µm have been prepared. Pore size impacts both compressive stiffness and frictional response. Silk hydrogels show significant interstitial fluid support under load and shear. The frictional response of cartilage can be reproduced by silk hydrogels. Wear and friction are not correlated for silk hydrogels.